2017
DOI: 10.4172/2167-7948.1000213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Ultrasound, Doppler, Elastography and Contrast Enhanced Ultrasonography Parameters with Histopathology Findings in the Differential Diagnosis of Benign and Malignant Thyroid Nodules

Abstract: Background: Though neck ultrasound is the first line of choice for the screening of thyroid nodules, very few studies have compared the diagnostic performances of both conventional and advanced ultrasound parameters. In this study, we aim to compare various conventional and advanced ultrasound imaging parameters and confirm it with histopathology findings to differentiate between benign and malignant thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Caruso et al stated that, while the systolic-peak velocities measured from the inferior thyroidal artery in Grave's disease were above 150 cm/sec, they reported that the peak velocities were within normal limits (< 65 cm/sec) in other common thyroid gland diseases including HT [23]. In our patient group, mean [26]. The mean RI of the HT group was 0.49 and the mean RI of the normal control group was 0.56, and the difference was considered significant.…”
Section: Discussionmentioning
confidence: 42%
“…Caruso et al stated that, while the systolic-peak velocities measured from the inferior thyroidal artery in Grave's disease were above 150 cm/sec, they reported that the peak velocities were within normal limits (< 65 cm/sec) in other common thyroid gland diseases including HT [23]. In our patient group, mean [26]. The mean RI of the HT group was 0.49 and the mean RI of the normal control group was 0.56, and the difference was considered significant.…”
Section: Discussionmentioning
confidence: 42%